Factor that affects the students performance in Mathematics subject using logistic regression / Norwaziah Mahmud ... [et al.] - Mahmud, Norwaziah; Muhammat Pazil, Nur Syuhada; Rosli, Nur Syakirah; Jamaluddin, Siti Hafawati (UiTM Cawangan Perlis, 2024)
Predicting students' academic performance plays an important role in academics. Mathematics is a science concerned with the logic of shape, quantity, and order. This subject holds a crucial role in the school curriculum. Mathematics is a basic knowledge that students should have the expertise in order for them to score in the other subjects. However, most students find Mathematics a difficult subject, they will have difficulty scoring in this subject. Therefore, this paper aims to determine the factors that affect students’ performance in Mathematics subject which is the pre-calculus subject among students of Diploma in Computer Sciences (CS110) in UiTM Cawangan Melaka Kampus Jasin. During the analysis, gender, assessment marks, place of students, time spent studying pre-calculus subject per week, whether the student took additional mathematics in SPM, act as independent variables whereas grade for pre-calculus subject as the dependent variable, were examined. The assessments refer to test 1, test 2, lab assignment, quiz 1, quiz 2 and written assignment. The logistic regression model was applied, and the results showed that the gender, test 2 and quiz 2 are variables that are significant to the model with the p-value 0.031,0.014 and 0.03 respectively. When examining the variables influencing the academic performance of CS110 students at UiTM Cawangan Melaka Kampus Jasin, there are certain knowledge gaps and restrictions. It is advised that future studies should collect data from more respondents and keep the question simple but clear in order to get more accurate results.